2009
DOI: 10.1111/j.1365-294x.2009.04422.x
|View full text |Cite
|
Sign up to set email alerts
|

The noncosmopolitanism paradigm of freshwater zooplankton: insights from the global phylogeography of the predatory cladoceran Polyphemus pediculus (Linnaeus, 1761) (Crustacea, Onychopoda)

Abstract: A major question in our understanding of eukaryotic biodiversity is whether small bodied taxa have cosmopolitan distributions or consist of geographically localized cryptic taxa. Here, we explore the global phylogeography of the freshwater cladoceran Polyphemus pediculus (Linnaeus, 1761) (Crustacea, Onychopoda) using two mitochondrial genes, cytochrome c oxidase subunit I and 16s ribosomal RNA, and one nuclear marker, 18s ribosomal RNA. The results of neighbour-joining and Bayesian phylogenetic analyses reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
70
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 86 publications
(143 reference statements)
11
70
0
1
Order By: Relevance
“…Nowadays, a large consensus is achieved on the fact that the cosmopolitanism paradigm has to give way to the evidences of pronounced ''regionalism'' or ''provincialism'' which emerged in almost all the investigated taxa (e.g. De Gelas & De Meester, 2005;Xu et al, 2009;Crease et al, 2012). At a within-species level, quite a low ongoing gene flow between conspecific populations is usually observed (Boileau et al, 1992), which contributes to the presence of marked phylogeographic structures in the vast majority of inland water taxa (e.g.…”
Section: Genetic Evidences About Dispersal and Colonizationmentioning
confidence: 99%
“…Nowadays, a large consensus is achieved on the fact that the cosmopolitanism paradigm has to give way to the evidences of pronounced ''regionalism'' or ''provincialism'' which emerged in almost all the investigated taxa (e.g. De Gelas & De Meester, 2005;Xu et al, 2009;Crease et al, 2012). At a within-species level, quite a low ongoing gene flow between conspecific populations is usually observed (Boileau et al, 1992), which contributes to the presence of marked phylogeographic structures in the vast majority of inland water taxa (e.g.…”
Section: Genetic Evidences About Dispersal and Colonizationmentioning
confidence: 99%
“…However, it has been demonstrated by others (2,3) that in general, unicellular eukaryote organisms such as protists and diatoms disperse over shorter geographical distances than larger multicellular organisms such as annelids, nematodes, and bivalves in both marine and terrestrial environments. A global molecular study of freshwater cladocerans found that continental and regional endemism is common and cosmopolitan species are rare (4). It was found that taxa described in the morphological literature as cosmopolitan are not homogeneous at the molecular level, suggesting that taxa previously identified as cosmopolitan can be an artifact resulting from inaccurate taxonomy, the presence of morphological stasis, or phenotype plasticity.…”
mentioning
confidence: 99%
“…In the Nearctic, the Pacific coast (e.g., Cascadia) and the Bering land bridge that joined present-day Alaska and eastern Siberia are well-known glacial refugia for a number of freshwater cladoceran species complexes, including Sida crystallina (Cox and Hebert 2001), Daphnia pulex (Weider and Hobaek 2003), Daphnia longispina (Ishida and Taylor 2007a), Daphnia galeata (Ishida and Taylor 2007b), Holopedium gibberum , and Polyphemus pediculus (Xu et al 2009). In addition, phylogenetic investigations have uncovered high levels of genetic diversity and endemism along the Pacific and Atlantic coasts of Canada (e.g., Queen Charlotte Islands and Nova Scotia) and in the Great Lakes and Mississippi regions (Hebert et al 2003;Dooh et al 2006), indicating the presence of glacial refugia in these areas.…”
mentioning
confidence: 99%
“…A classical southern refuge (e.g., Iberian Peninsula) was likely important for the rotifer Brachionus manjavaca (Gomez et al 2007). However, for the isopod Asellus aquaticus and the cladoceran P. pediculus, it has been suggested that the Pannonian basin of central Europe (Verovnik et al 2005) and the region north of the Ponto-Caspian basin (Xu et al 2009) harbored refugial populations that subsequently recolonized large parts of the west Palearctic. Moreover, four moderately divergent and geographically distinct lineages of Daphnia magna were identified in Europe.…”
mentioning
confidence: 99%